Familie, școală și succes școlar în învățământul liceal românesc - Țoc, Sebastian (Calitatea Vieții, 2016)
In this paper I use the Programme for International Student Assessment (PISA) database to test which factors influence the academic performance of 15 years old Romanian students. This study contributes to the larger debate in the field of sociology of education concerning the role of school and family resources in determining student achievement. The results show that the best explanatory variables are occupational status of parents and cultural possessions at home. Among the school related factors, quality of educational resources, an index developed based on the principals’ perceptions regarding the availability of instruction materials in their school, have a moderate effect. The analysis confirms the hypothesis that educational results are influenced more by family related factors than school related factors. The conclusions are also important from a policy perspective, bearing in mind that reducing the educational inequalities in Romania is considered a priority. So far national programs tried to improve school resources such as infrastructure or quality of teaching, but they failed in reducing the performance gap. This article suggests that factors outside the school should be taken into consideration in order to improve access to education and reduce educational inequalities.